Quality of experience aware multimedia communications over heterogeneous wireless networks. Issue 2 (1st March 2016) - Pierre, Setton
Abstract : Quality of experience (QoE) has been a user‐centric performance metric for multimedia communications. Existing communication protocols over heterogeneous networks are mostly based on quality of service, which ignores the user satisfaction and subjective evaluation. In this paper, the authors propose a novel QoE‐aware multimedia communication framework for heterogeneous wireless networks. Specifically, the authors make three main contributions in this paper: (i) a general QoE model has been established by jointly characterising the multimedia applications and heterogeneous networks, (ii) the issue of multimedia communications over heterogeneous networks has been transformed as a stochastic optimisation problem, and (iii) the optimal solution is provided by designing a QoE‐aware multimedia scheduling scheme. Importantly, the proposed scheme is simply enough for online implementation. Numerical simulations have demonstrated the efficiency and robustness of the proposed scheme.